Case report: Dravet syndrome, feeding difficulties and gastrostomy - Clayton, Lisa M.; Williams, Edwina; Balestrini, Simona; Sisodiya, Sanjay M. (Frontiers in Neurology, 2022)
Dravet syndrome (DS) is a developmental and epileptic encephalopathy associated with variants in the voltage-gated sodium channel alpha 1 subunit (SCN1A) gene in around 90% of individuals. The core phenotype is well recognized, and is characterized by seizure onset in infancy, typically with prolonged febrile seizures, followed by the emergence of multiple seizure types that are frequently drug-resistant, developmental delay, and intellectual disability. Comorbidities are common and include autism spectrum disorder, gait impairment, scoliosis, and sleep disorder. Feeding difficulties and weight loss are frequently reported by DS caregivers, and negatively impact quality of life, yet have received little attention. Here we report an adult with DS who developed reduced food and fluid intake in adolescence, resulting in weight loss and malnutrition. No underlying cause for her feeding difficulties was identified, and she subsequently required insertion of a percutaneous endoscopic gastrostomy. We review the occurrence of feeding difficulties in people with DS and discuss potential mechanisms.